Memposisikan kembali minat literasi untuk mewujudkan upaya berpikir kritis - Sutiasih, Nur Maulia Sari (Maliki Interdisciplinary Journal, 2023)
Writing this article aims to analyze the causes of the low interest in literacy in Indonesian society and provide solutions, as well as developing Problem Based Learning (PBL) learning to improve critical thinking skills. Based on data in journals as a reference in developing early childhood literacy interest, namely the method of using books with illustrated pictures is more effective and easier to understand. In addition, the development of learning using the Problem Based Learning (PBL) method will encourage students to be able to think critically in solving a problem and require them to find solutions through appropriate books. Through the development of literacy interest, it will greatly encourage students to develop critical thinking. So that this will also be a guide for a nation to continue to develop as well as progress. Literacy and critical thinking factors are very influential in advancing a nation. Because by reading a lot, there will be more information and knowledge that can be developed, and by thinking critically, we will not be easily influenced by information that is not necessarily true. Critical thinking will also encourage you to be able to solve problems that are being faced by the state or government and find solutions.